Evidence Based Public Health on the example of vaccinations - theory and practice - Wrześniewska-Wal, Iwona; Kobuszewski, Bartosz (Journal of Education, Health and Sport, 2021)
The aim of the review was to present one of the basic tools of public health, which are vaccinations, from the point of view of scientific evidence regarding their safety. This problem is closely related to health safety and the constitutional obligation of the state to ensure the protection of health and life (Article 68 of the Polish Constitution). It is important that, unlike other medicines, vaccinations are given to healthy people, and many of them are given to children. The first part of the article shows the impact of scientific discoveries in the field of infectious diseases, including discoveries in the field of vaccinations, on the prevention of infections and the development of legal regulations ensuring patient safety. The history of the legislation on public health and the current legal solutions of the European Union and Poland are also briefly presented. Part two introduces Evidence Based Public Health (EBPH) practice, encompassing complex processes that aim to improve population health and reduce the burden of disease. The last element of the work is the quantitative analysis of adverse vaccine reactions (NOP) reported in recent years in Poland, the monitoring of which is the basic tool for assessing vaccine safety in actual clinical practice. The current reporting procedure was also presented.